1997
DOI: 10.1080/135468097396270
|View full text |Cite
|
Sign up to set email alerts
|

Testing vs. Believing Hypotheses: Magical Ideation in the Judgement of Contingencies

Abstract: This paper examines the idea that an important dimension of human cognition is the amount of objective evidence required for perception of meaningful patterns. At the clinical extreme of this dimension are patients with hallucinations and delusions who experience perception with no external evidence and see connections between objectively unrelated events. Also, normal individuals exhibit considerable variation along this continuum. The theory proposed here predicts that normal subjects with low evidential cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 61 publications
10
87
2
4
Order By: Relevance
“…This means that they evidenced a tendency to say "yes" rather than "no," or in more general terms, favored a Type I error over a Type II error strategy. Such an inclination is in accordance with previous research with healthy persons endorsing paranormal beliefs (Reed et al, 2008;Tsakanikos & Reed, 2005;Wiseman, Greening, & Smith, 2003;Weinstein & Graves, 2002;Brugger & Graves, 1997b). Although a reduced criterion may be adaptive in detecting real associations and develop novel links between concepts (Folley & Park, 2005;Folley, Doop, & Park, 2003;Weinstein & Graves, 2001Gianotti et al, 2001;Claridge et al, 1990), it simultaneously bears the risk of false causal attributions and lowers the threshold for hallucinatory perceptual experiences (Bell et al, 2007;Brugger & Graves, 1997b).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This means that they evidenced a tendency to say "yes" rather than "no," or in more general terms, favored a Type I error over a Type II error strategy. Such an inclination is in accordance with previous research with healthy persons endorsing paranormal beliefs (Reed et al, 2008;Tsakanikos & Reed, 2005;Wiseman, Greening, & Smith, 2003;Weinstein & Graves, 2002;Brugger & Graves, 1997b). Although a reduced criterion may be adaptive in detecting real associations and develop novel links between concepts (Folley & Park, 2005;Folley, Doop, & Park, 2003;Weinstein & Graves, 2001Gianotti et al, 2001;Claridge et al, 1990), it simultaneously bears the risk of false causal attributions and lowers the threshold for hallucinatory perceptual experiences (Bell et al, 2007;Brugger & Graves, 1997b).…”
Section: Discussionsupporting
confidence: 70%
“…For instance, individuals with paranormal belief evidence a marked willingness to perceive "patterns in noise" (Reed et al, 2008;Bell, Reddy, Halligan, Kirov, & Ellis, 2007;Brugger & Graves, 1997b) and are more inclined than those skeptical about such abilities to attribute meaning to random associations (Mohr, Landis, & Brugger, 2006;Gianotti, Mohr, Pizzagalli, Lehmann, & Brugger, 2001;. Although the creative aspects of paranormal thought have been emphasized by some authors (Folley & Park, 2005;Weinstein & Graves, 2002;Gianotti et al, 2001;Claridge, Pryor, & Watkins, 1990), others have equally stressed its conceptual similarity to psychotic symptoms (Brugger & Graves, 1997b;Kreweras, 1983). Thus, a reduced criterion to acknowledge the presence of a signal not only increases the chances to creatively detect a real stimulus but also bears the risk of Type II errors, that is, hallucinatory perceptions and delusional inferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, using a word association task, Gianotti et al (2001) found that believers in a variety of paranormal phenomena produced more idiosyncratic words or more distant associations than did skeptics. It also has been suggested that some kinds of paranormal beliefs -and particularly paranormal experiences -might be related to abnormal neurocognitive development or schizotypy (see Brugger & Graves, 1997). While we did find a link between psychic beliefs and personality characteristics such as dissociative experiences and absorption, which may relate to these other cognitive factors, we did not directly investigate these other cognitive factors in the current study.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Saxe et al, 2004Bear et al, 1982Bear & Fedio, 1977Britton & Bootzin, 2004Persinger & Makarec, 1987Lehmann, et al, 2001Aftanas & Golocheikine, 2001Wuerfel et al, 2004Brugger & Graves, 1997Fenwick et al, 1985MacDonald & Holland, 2002Morneau et al, 1996Persinger, 1984 …”
Section: Arguments For the "Producing" Point Of Viewmentioning
confidence: 99%